The iSpring Suite 9: Its Effect on EFL Learners in Comprehending Narrative Text - Fita Fitriati; Fika Megawati (Borneo Educational Journal (Borju), 2021)
The research is to find out the effect of using interactive learning multimedia with iSpring Suite 9 to improve motivation and civics education learning outcome in one of state vocational schools. The population is all of the students in tenth grade. The sample is Multimedia 1 as the experimental Class and Multimedia 2 as the control class. Both of two classes consist thirty six students. The research methodology used in this research is experiment research method with quantitative approach. The used experiment method form is Quasi Experimental design. Data collection instrument for learning narrative text uses 10 multiple choices questions, while learning outcome is done by test. The data collection was taken from pre-test and post-test using online learning especially WhatsApp group. The research result data are previously done by making normality test, homogeneity test and T test. Data analysis uses T test with Microsoft excel 2007. The average score of experimental group is 81.66, and the average score of control group is 68.22. Moreover, the hypothesis test shows that Ho is rejected because t count (4.71) is higher than t tab (2.28) . The result of this study indicates that using iSpring Suite 9 gives significant effect to teach narrative reading skill. Keywords: iSpring Suite 9, WhatsApp Group, Narrative Text.